2016
DOI: 10.18632/oncotarget.10524
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-93-5p may participate in the formation of morphine tolerance in bone cancer pain mouse model by targeting Smad5

Abstract: ObjectiveIn this study, we aim to find out the role of microRNA-93-5p (miR-93) and Smad5 in morphine tolerance in mouse models of bone cancer pain (BCP).ResultsAt 7 days after injection of morphine, the PMWT showed no significant difference between the morphine model group and the saline model group (P < 0.05), suggesting that morphine tolerance had formed in the morphine model group. The morphine model group had higher miR-93 expression and lower Smad5 mRNA expression than the saline model group. Smad5 is a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…In the present study, we demonstrated that the expression of miR-93 was significantly increased in NPC cell lines and tumor tissues. The evidence indicates that miR-93 was upregulated in NPC, which is consistent with the results obtained from bone cancer ( 15 ), myocardial ischemia/reperfusion (I/R) injury ( 14 ) and polycystic ovarian syndrome ( 22 ). The enhanced proliferation of NPC cell lines indicated that miR-93 was an oncogene in NPC.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the present study, we demonstrated that the expression of miR-93 was significantly increased in NPC cell lines and tumor tissues. The evidence indicates that miR-93 was upregulated in NPC, which is consistent with the results obtained from bone cancer ( 15 ), myocardial ischemia/reperfusion (I/R) injury ( 14 ) and polycystic ovarian syndrome ( 22 ). The enhanced proliferation of NPC cell lines indicated that miR-93 was an oncogene in NPC.…”
Section: Discussionsupporting
confidence: 88%
“…These findings indicated that the abnormally expressed miRNAs may contribute to the progression and development of NPC. miR-93, derived from a paralogue (miR-106b-25), is dysregulated in several cancer types, such as epithelial ovarian carcinoma ( 13 ), ischemic heart disease ( 14 ) and bone cancer pain mouse model ( 15 ). The evidence indicates that miR-93 plays a key role in cancer progression.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, high expression of miR-195 suppresses tumor growth in prostate carcinoma in vivo (42). SMAD5 could serve as a target of miRNA to inhibit the angiogenesis, thereby contributing to tumor growth and metastases (43).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, anti-miR-93 alleviated morphine tolerance. Overall, Up-regulation of miR-93 may contribute to the progression of morphine tolerance by targeting Smad5 in mouse bone cancer pain (Xiao et al, 2016 ). Morphine tolerance was remarkably suppressed in pLV-THM-miR-338 rats with lower expression of CXC chemokine receptor-4 (CXCR4).…”
Section: Relevance Of Mirna-based Mechanisms In Morphine Tolerancementioning
confidence: 99%